Pharmacokinetic/pharmacodynamic based dosing of ciprofloxacin in complicated urinary tract infections - Ana Sabo; Ana Tomas; Nataa Tomi?; Momir Mikov; Olga Horvat; Radmila Popovi?; Zdenko Tomi? (Bangladesh Pharmacological Society, 2015)
Ciprofloxacin is often used in treatment of complicated urinary tract infections in areas with high rates of resistance to first line agents. The aim of this study was to evaluate efficacy of ciprofloxacin in standard dosing regimens in treatment of complicated urinary tract infections. Plasma concentration curves were simulated and minimum inhibitory concentration (MIC) and post-antibiotic effect were determined. Ciprofloxacin MIC ranged from 0.0156 for Gram-negative and to 0.125-0.5 µg/mL for Gram-positive bacteria. Both dosing regimens were suitable for eradication of Gram-negative bacteria, with slight supremacy of 750 mg/12 hours over 500 mg/12 hours dosing regimen. Even though all strains were fully susceptible to ciprofloxacin, pharmaco-kinetic/pharmacodynamic parameters did not meet target thresholds for pathogens with MIC over 0.1-0.2 µg/mL regardless of the administered dose. Ciprofloxacin remains an excellent choice for treatment of complicated urinary tract infections caused by Gram-negative bacteria, but in infection caused by Gram-positive strains, deeper analysis is necessary in order to achieve optimal results.